LITERACY OF MATHEMATICAL STORY PROBLEMS ON PROBLEM SOLVING SKILLS OF ELEMENTARY SCHOOL STUDENTS - Widia Nur Jannah; Tatang Herman; Mubiar Agustin; Vismaia S. Damaianti (Jurnal Cakrawala Pendas, 2025)
In Indonesia, understanding math story problems is often a challenge for many students, especially in connecting the information given in the problem with relevant mathematical concepts. This suggests a need to improve students' literacy in understanding mathematical story problems in order to better solve problems. Therefore, this study aims to analyse and describe the relationship between literacy in math word problems and fourth-grade students' problem-solving skills. This research uses a quantitative approach with a correlational research design. The variables studied were literacy in understanding math word problems as the independent variable and problem-solving ability as the dependent variable. The research sample consisted of 25 fourth-grade students from SD Negeri Pelandakan I. Purposive sampling was employed in this study. The research instruments utilised were observation sheets to assess students' reading literacy on math word problems and tests to assess fourth-grade students' problem-solving abilities. The findings of this study is based on the value of r_count and r_table, it is known that r_count ˃ r_table which shows that this study has proven a positive and significant correlation between literacy of math word problems with problem-solving skills of grade IV students of SDN Pelandakan I Cirebon. This is evidenced by the obtained r_count of 0.695. At a significance level of 1% (23), r_table is 0.413. The conclusion is concluded that enhanced literacy skills in reading math word problems correlate with improved problem-solving abilities among fourth-grade students, and conversely, reduced literacy skills align with diminished problem-solving abilities. The theoretical implication of the results of this study is that it confirms the belief in the importance of students' literacy skills and problem-solving abilities in addressing math word problems.